2007
DOI: 10.2527/jas.2005-750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distillers grains or corn supplementation frequency on forage intake and digestibility1

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 26 publications
8
45
2
Order By: Relevance
“…However, Radev (2012) found that dietary supplementation with DDGS increased rumen ammonia concentration in sheep. Similar effect was reported by Loy et al (2007) in the in vivo study in heifers. Converse results were obtained by Li et al (2014) who proved that feeding DDGS to laying hens resulted in 14% fall in ammonia emission.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, Radev (2012) found that dietary supplementation with DDGS increased rumen ammonia concentration in sheep. Similar effect was reported by Loy et al (2007) in the in vivo study in heifers. Converse results were obtained by Li et al (2014) who proved that feeding DDGS to laying hens resulted in 14% fall in ammonia emission.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, replacement of silage or barley grain with DDGS did not affect the total production and changes in the profile of SCFAs in the rumen of cows (Zhang et al 2010). The results of other studies showed that increasing DDGS content in the fermentation substrate lowered acetate with an increase in propionate and butyrate rumen production , Loy et al 2007. The in vitro studies showed that the use of DDGS decreased acetate and propionate levels in lambs (Behlke 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Given these calculations, the TDN value of DRC decreased from 90% at the LOW supplement concentration to 81% at the HIGH supplement concentration. This is likely due to the negative effect of starch and pH on cellulolytic activity (Loy et al, 2007). Although the decline in TDN was charged to the corn in our cal- culations, the decline in digestibility (TDN) was likely due to a decline in the digestibility of fiber of the hay.…”
Section: Prediction Of Energy Value Of Supplementsmentioning
confidence: 69%
“…We theorize that this decline is due to the fat content of the DDGS and the subsequent effect on ruminal cellulolytic activity (Loy et al, 2007). The fat of the HIGH DDGS diet was about 5.2%.…”
Section: Prediction Of Energy Value Of Supplementsmentioning
confidence: 97%
“…However, ethanol production from corn grain has made dried distillers grains (DDG) an available feedstuff that improves growth rate of grazing cattle (Griffin et al, 2012). In addition to demonstrating an increase in animal performance, previous research has demonstrated a substitution effect on forage intake when DDG is fed in forage-based diets (Loy et al, 2007;MacDonald et al, 2007;Griffin et al, 2012). If the cost of DDG is less than the cost of replaced grazed forage on a per unit of energy basis, then cost of production could be decreased by feeding DDG.…”
Section: Introductionmentioning
confidence: 99%